Minat Calon Pengantin Terhadap Penggunaan Kontak Lensa Pada Tata Rias Pengantin - Bidhari Sinta Mei Sasti; Titin Supiani (Universitas Negeri Jakarta, 2023)
Interest of Prospective Brides in Using Contact Lenses in Bridal Makeup. Final Project. Jakarta: Diploma Three Makeup Study Program, Faculty of Engineering, Jakarta State University, 2021. This study aims to determine the extent of interest of prospective brides in using contact lenses in bridal makeup. The study population consists of prospective brides who registered to marry in 2021 at three studios: LKP Giyama Makeup Studio, Mbak Endang Makeup & Decoration Studio, and Ophen House Manten Makeup Studio, with a total sample of 38 people. This study uses a quantitative descriptive method by distributing questionnaires via Google Form to respondents. Thus, the results of the study obtained from 6 aspects of prospective brides' interest in the use of contact lenses in bridal makeup are that the aspect of feeling interested is 75.65% of the interested criteria, attention is 65.86% of the very hesitant criteria, feelings of pleasure are 73.28% of the interested criteria, hopes are 88.42% of the very interested criteria, needs are 75.36% of the interested criteria, and motivation is 83.3% of the interested criteria and the results of regional domicile data show that Bekasi obtained 99.68% results and Blora obtained 74.71% results. So it can be concluded that the interest of prospective brides in using contact lenses in bridal makeup has an overall percentage of 76.97%, which falls into the interested criteria, and the interest of prospective brides for the Bekasi domicile is higher, falling into the very interested category, compared to Blora, falling into the interested category.